Prediksi Harga Emas Antam menggunakan Metode Regresi Linear: Indonesia - Yulianti; Bihablila; Rahmah, Siti; Lissa, Hermei (Jurusan Matematika dan Teknologi Informasi, 2025)
Gold is one of the most popular and considered safe investment instruments due to its long-term value stability. However, gold prices still experience fluctuations influenced by various economic and geopolitical factors. Therefore, the ability to predict gold prices is crucial for investors, traders, and jewelry industry players. This study aims to predict the selling price of Antam gold using a simple linear regression method based on historical data of buying and selling prices during the period of March 31 to April 7, 2025. The analysis shows a positive linear relationship between buying and selling prices, with the regression equation Y = 8.660,47 + 0,97X . The model yields predictions that closely approximate actual values, with a Mean Absolute Deviation (MAD) of Rp 2,328.91 and an accuracy rate of 99.86%. These findings indicate that simple linear regression can be an effective and accurate tool for short-term gold price forecasting and can serve as a basis for investment decision-making.